Comparing the efficacy and safety of medications in adults with hypertrophic cardiomyopathy: a systematic review and network meta-analysis - Mi, Keying; Wu, Sijia; Lv, Chanyuan; Meng, Yongkang; Yin, Wenchao; Li, Hongkai; Li, Jiangbing; Yuan, Haitao (Frontiers in Cardiovascular Medicine, 2023)
Background Hypertrophic cardiomyopathy (HCM) is the most common genetic heart disease. The purpose of this study was to evaluate the efficacy and safety of several medications and recommend better drug treatments for adults with HCM. Methods A review of PubMed, Embase, the Cochrane Controlled Register of Trials (CENTRAL), ClinicalTrials.gov and CNKI databases was conducted for studies on the efficacy and safety of drugs for adults with HCM. A frequentist random effects model was used in this network analysis. Results This network meta-analysis included 7 studies assessing seven medications, 6 studies evaluating monotherapy and 1 study evaluating combination therapy. Based on the network meta-analysis results, xiaoxinbi formula plus metoprolol (MD −56.50% [−72.43%, −40.57%]), metoprolol (MD −47.00% [−59.07%, −34.93%]) and mavacamten (MD −34.50% [−44.75%, −24.25%]) significantly reduced the resting left ventricular outflow tract gradient (LVOTG) in comparison with placebo. Resting LVOTG could also be reduced with N-acetylcysteine (NAC). The incidence of adverse drug reactions was not significantly different between the placebo group and the treatment group. Conclusion For adults with HCM, the top 4 treatments included xiaoxinbi formula plus metoprolol, metoprolol, mavacamten and NAC. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=374222], identifier [CRD42022374222].